Epidemiological Characterization of Clinical Fungal Isolates from Pauls Stradinš Clinical University Hospital, Latvia: A 4-Year Surveillance Report - Nityanand Jain; Inese Jansone; Tatjana Obidenova; Raimonds Sīmanis; Jānis Meisters; Dagnija Straupmane; Aigars Reinis (Life, 2021)
Nosocomial fungal infections are an emerging global public health threat that requires urgent attention and proper management. With the limited availability of treatment options, it has become necessary to understand the emerging epidemiological trends, mechanisms, and risk factors. However, very limited surveillance reports are available in the Latvian and broader European context. We therefore conducted a retrospective analysis of laboratory data (2017–2020) from Pauls Stradinš Clinical University Hospital (PSCUH), Riga, Latvia, which is one of the largest public multispecialty hospitals in Latvia. A total of 2278 fungal isolates were analyzed during the study period, with Candida spp. comprising 95% of the isolates, followed by Aspergillus spp. and Geotrichum spp. Amongst the Candida spp., C. albicans and C. glabrata made up about 75% of the isolates. The Department of Lung Diseases and Thoracic Surgery had the highest caseload followed by Intensive Care Department. Majority of the fungal isolates were collected from the bronchoalveolar lavage (37%), followed by urine (19%) and sputum (18%) samples. A total of 34 cases of candidemia were noted during the study period with C. albicans being the most common candidemia pathogen. Proper surveillance of emerging epidemiological trends serve as the most reliable and powerful cornerstone towards tackling this emerging threat.